Magnetic nanoparticle-based approaches to locally target therapy and enhance tissue regeneration in vivo. (September 2012) - Sensenig, Richard; Sapir, Yulia; MacDonald, Cristin; Cohen, Smadar; Polyak, Boris
Magnetic-based systems utilizing superparamagnetic nanoparticles and a magnetic field gradient to exert a force on these particles have been used in a wide range of biomedical applications. This review is focused on drug targeting applications that require penetration of a cellular barrier as well as strategies to improve the efficacy of targeting in these biomedical applications. Another focus of this review is regenerative applications utilizing tissue engineered scaffolds prepared with the aid of magnetic particles, the use of remote actuation for release of bioactive molecules and magneto–mechanical cell stimulation, cell seeding and cell patterning.